Розробка компонентів системи підтримки прийняття рішень у сфері закупівлі озброєння та військової техніки - Бзот, С. В. (ХНУРЕ, 2024)
In the conditions of the continuation of Russia's armed aggression against Ukraine, the level of existing and potential military threats to national security is constantly increasing and requires significant efforts to increase the defense capabilities of our country. The contradiction between the limited financial capabilities of the state and the growing needs of the Armed Forces is proposed to be resolved using modern information technologies and algorithms that can be implemented in the decision support system. The development of the components of such a system and the algorithms of its operation will allow to increase the effectiveness and validity of decisions in the field of procurement of weapons and military equipment.
Keywords: сиситема підтримки; СППР; сфера закупівлі; озброєння; військова техніка